CHARACTER EDUCATION OF STUDENTS THROUGH THE CULTURE OF GREETING IN AN ETHNOGRAPHIC PERSPECTIVE AT MODERN BOARDING SCHOOL AL-ISHLAH BONDOWOSO - Fatahillah Arrozi (Tsaqofah : Jurnal Pendidikan Islam, 2024)
The purpose of this study is to find out how character education is applied in the formation of a greeting culture, and how the character of students is formed in the cultural system. This study uses a qualitative descriptive approach with an ethnographic research design. The data collection technique is done through observation and in-depth interviews. The data analysis technique in this study uses the Miles and Huberman model with three stages. Namely: a. Data reduction. b. Data Presentation. c. Conclusion Withdrawal. Character education through the culture of saying greetings at the Al-Ishlah Islamic Boarding School turned out to produce santri characters who can love each other with their fellow Muslims, have a polite and courteous attitude, and have a ta'dzim attitude towards kyai, asatidz, and older people. Keywords: , ,